Efficacy of Some Post-emergence Herbicides and their Mixtures Against Complex Weed Flora in Wheat - Mathukia, Ratilal K.; Sagarka, Bhimjibhai K.; Panara, Dhirubhai M.; Gohil, Bhagirathsinh S. (International Journal of Economic Plants, 2018)
A field experiment was conducted during rabi season of 2015–16 at Junagadh (Gujarat) to evaluate efficacy of some post-emergence herbicides (metsulfuron, isoproturon, clodinafop, fenoxaprop) and their mixtures (sulfosulfuron+metsulfuron, clodinafop+metsulfuron, isoproturon+metsulfuron, isoproturon+fenoxaprop, isoproturon+clodinafop) against complex weed flora in wheat. The dominant weed flora noticed in the experimental field were Echinochloa colona, Cynodon dactylon, Brachiaria spp. and Dactyloctenium aegyptium among the monocots; Amaranthus viridis, Chenopodium album, Digera arvensis, Melilotus indica, Portulaca oleracea, Convolvulus arvensis, Euphorbia hirta and Phyllanthus niruri among the dicot weeds and Cyperus rotundus as sedge weed. The results revealed that hand weeding (HW) at 15 and 30 DAS, HW at 15 DAS fb pre-mix sulfosulfuron+metsulfuron (25 g ha-1) at 30 DAS, and HW at 15 DAS fb pre-mix clodinafop+metsulfuron (32 g ha-1) at 30 DAS were found superior treatments next to the weed free check in controlling weeds and improving growth and yield attributes and ultimately grain and straw yields of wheat. It is suggested that pre-mix sulfosulfuron + metsulfuron or clodinafop+metsulfuron could be used to control broad spectrum of weeds in wheat. The herbicide mix could be helpful in reducing herbicide residue in soil and prevent or delay the development of herbicide resistance weeds.